A Rare Case of Polyostotic Fibrous Dysplasia Assessed by Bone Scintigraphy with Tc-99m Methylene Diphosphonate (MDP) - Di Leo, C.; Ardemagni, A.; Bestetti, A.; Tagliabue, L.; Del Sole, A.; Conte, A.; Tarolo, G. L. (Nuklearmedizin - NuclearMedicine, 1999)
A 66-year-old man affected by polyostotic form of fibrous dysplasia in consequence of worsening of lower extremity bone pain aggravated by walking and concomitant increase of serum alkaline phosphatase and osteocalcin, was subjected first to a radionuclide study. Bone scan demonstrated a pathological uptake of the radiotracer in the craniofacial bones, right scapula, left and right posterior ribs, right hemipelvis and lower extremities confirming the diagnosis but establishing especially the extent of bone involvement, greater than expected on the basis of symptoms and X-ray findings, underlying the importance of nuclear medicine imaging in the assessment and follow-up of this rare disease.
Keywords: Fibrous dysplasia; McCune-Albright Syndrome; bone scintigraphy